2016
DOI: 10.1105/tpc.16.00487
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Phytochrome B Inhibits Hypocotyl Negative Gravitropism Non-Cell-Autonomously

Abstract: Seedling hypocotyls display negative gravitropism in the dark but agravitropism in the light. The Arabidopsis thaliana pif quadruple mutant (pifQ), which lacks four PHYTOCHROME-INTERACTING FACTORS (PIFs), is agravitropic in the dark. Endodermis-specific expression of PIF1 rescues gravitropism in pifQ mutant seedlings. Since phytochromes induce light responses by inhibiting PIFs and the COP1-SPA ubiquitin E3 ligase complex in the nucleus, we asked whether phyB can cell autonomously inhibit hypocotyl negative gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 94 publications
0
51
0
Order By: Relevance
“…In general, phytochromes induce the rapid degradation of PIFs in response to light signals via direct physical interactions with PIFs (Al-Sady et al, 2008;Shen et al, 2008), although phyB has been shown to induce PIF1 degradation non cell autonomously (Kim et al, 2016b). DNA binding is not necessary for the light-induced degradation of PIFs (Al-Sady et al, 2008;Shen et al, 2008).…”
Section: Factors Controlling Pif Abundance Under Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, phytochromes induce the rapid degradation of PIFs in response to light signals via direct physical interactions with PIFs (Al-Sady et al, 2008;Shen et al, 2008), although phyB has been shown to induce PIF1 degradation non cell autonomously (Kim et al, 2016b). DNA binding is not necessary for the light-induced degradation of PIFs (Al-Sady et al, 2008;Shen et al, 2008).…”
Section: Factors Controlling Pif Abundance Under Lightmentioning
confidence: 99%
“…Interestingly, a recent study performed ChIP followed by microarray (ChIP-chip) to identify in vivo binding sites of PIF1 (Kim et al, 2016b). This study showed that PIF1 DNA-binding sites (PBSs) are enriched with not only G-boxes but also with other hexameric sequence elements named GCEs.…”
Section: Factors Enhancing the Dna-binding Ability Of Pifsmentioning
confidence: 99%
“…Conversely, PIFs are phosphorylated, poly-ubiquitylated and subsequently degraded under light (Leivar and Quail, 2011;Xu et al, 2015). However, a recent study has shown that phyB can induce degradation of PIF1 non-cell-autonomously (Kim et al, 2016b). Among the candidate kinases, oat phyA has been shown to directly phosphorylate PIFs and regulate the light-induced degradation of PIF3 under far-red light (Shin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although phyB seems to be expressed ubiquitously, there is some evidence that phyB effects may not be cell-autonomous, and certain downstream responses to red light perception by phyB must involve signaling between cells and between tissues. New work from Kim et al (2016) suggests that several effects mediated by phyB can be attributed to phyB in the epidermis.…”
mentioning
confidence: 99%
“…ep, epidermis; co, cortex; en, endodermis; vs, vascular structure. (Adapted from Kim et al [2016], Figure 1A.) OPEN Articles can be viewed without a subscription.…”
mentioning
confidence: 99%